Associations between nutritional and immune status and clinicopathologic factors in patients with tuberculosis: A comprehensive analysis - Liu, Quan-Xian; Tang, Dao-Yan; Xiang, Xi; He, Jian-Qing (Frontiers in Cellular and Infection Microbiology, 2022)
Objective This study was designed to assess and analyze nutritional status (NS) and immune status in patients with tuberculosis. Methods A retrospective analysis was conducted on 93 TB patients hospitalized in the tuberculosis ward of the West China Hospital of Sichuan University. Subgroup comparisons were made according to age (<65 years and ≥65 years), nutritional risk score 2002 (NRS 2002 <3 and ≥3), tuberculosis location [pulmonary tuberculosis and extrapulmonary tuberculosis (including pulmonary tuberculosis complicated with extrapulmonary tuberculosis)], and prognostic nutrition index (PNI) (<45 vs ≥45). Results Significantly increased weight loss was associated with extrapulmonary tuberculosis (P =0.0010). Serum albumin (P =0.0214), total lymphocyte count (P = 0.0009) and PNI (P = 0.0033) were significantly decreased in older patients. Neutrophils/lymphocytes (NLR) (P =0.0002), monocytes/lymphocytes (MLR) (P < 0.0001), and platelets/lymphocytes (PLR) (P =0.0107) were higher. According to NRS 2002, higher nutritional risk was associated with lower body weight and body mass index (BMI) (P < 0.0001), higher weight loss (P = 0.0012), longer duration of hospitalization (P =0.0100), lower serum albumin level and hemoglobin concentration (P <0.01), lower creatinine level, and lower PNI (P < 0.01). 0.0001), lower total lymphocyte count (P = 0.0004), higher neutrophil and monocyte counts (P <0.05), and higher NLR (P = 0.0002), MLR (P = 0.0006), and PLR (P = 0.0156). Lower PNI was associated with lower body weight (P = 0.0001) and BMI (P =0.0074), lower total protein, albumin, and hemoglobin concentrations (P < 0.0001), and lower total lymphocyte count (P < 0.0001) and creatinine levels (P = 0.0336), higher age (P =0.0002) and NRS 2002 score, P < 0.0001), longer hos-pital stay (P = 0.0003), higher neutrophil count (P = 0.0042), and NLR, MLR, and PLR (P <0.0001) were significantly correlated. In multivariate logistic regression analysis, weight loss (OR: 0.209, 95% CI: 0.060-0.722; p =0.013) was significantly associated with higher nutritional risk (NRS 2002≥3). In multiple linear regression analysis, the NRS 2002 score was higher (B=2.018; p =0.023), and extrapulmonary tuberculosis (B=-6.205; p =0.007) was linked with a longer duration of hos-pitalization. Conclusions Older tuberculosis patients are at nutritional risk, and older patients (≥65 years old) need to pay attention to nutritional monitoring and intervention. Older TB patients and those at risk of malnutrition have increased immune ratio and impaired immune function. Management of TB patients using basic diagnostic tools to assess nutritional and immune status and calculate PNI and immunological indexes (NLR, MLR, PLR) to improve treatment outcomes.